Property improvements of CNT films induced by wet-stretching and tension-heating post treatments. (December 2017) - Wang, Shaokai; Liu, Qianli; Li, Min; Li, Tianshu; Gu, Yizhuo; Li, Qingwen; Zhang, Zuoguang
Abstract: Various stretching and heating treatments were conducted on a carbon nanotube (CNT) film, so as to transfer the excellent properties of individual CNTs into a useful material. It shows that the wet-stretching improves the tensile strength and modulus to 2.3 and 5.9 times of the CNT film treated by traditionally dry stretching. Inspired by carbonization process of carbon fiber, tension force was further applied on the CNT film during subsequent heat treatment. Therefore, tensile strength and modulus of the CNT film are dramatically improved to 6.3 and 39.7 times respectively comparing with the as-prepared film. The tensile modulus reaches up to 127.1 GPa, far beyond most reported moduli of nanocarbon-based films and papers. Herein, the higher tensile moduli of the post-treated CNT films the smaller fracture elongation. Moreover, the post-treated CNT film manifests stable piezoresistive behavior with the gauge factor of 13.2, indicating of good sensitivity of the network.